N-glycosylation in Haloferax volcanii: adjusting the sweetness - Eichler, Jerry; Arbiv, Adi; Cohen-Rosenzweig, Chen; Kaminski, Lina; Kandiba, Lina; Konrad, Zvia (Frontiers in Microbiology, 2013)
Long believed to be restricted to Eukarya, it is now known that cells of all three domains of life perform N-glycosylation, the covalent attachment of glycans to select target protein asparagine residues. Still, it is only in the last decade that pathways of N-glycosylation in Archaea have been delineated. In the haloarchaeon Haloferax volcanii, a series of Agl (archaeal glycosylation) proteins is responsible for the addition of an N-linked pentasaccharide to modified proteins, including the surface (S)-layer glycoprotein, the sole component of the surface layer surrounding the cell. The S-layer glycoprotein N-linked glycosylation profile changes, however, as a function of surrounding salinity. Upon growth at different salt concentrations, the S-layer glycoprotein is either decorated by the N-linked pentasaccharide introduced above or by both this pentasaccharide as well as a tetrasaccharide of distinct composition. Recent efforts have identified Agl5-Agl15 as components of a second Hfx. volcanii N-glycosylation pathway responsible for generating the tetrasaccharide attached to S-layer glycoprotein when growth occurs in 1.75 M but not 3.4 M NaCl-containing medium.